Intracellular Proprotein convertase subtilisin/kexin type 9: Recruitment and regulatory role in mitochondrial architecture and bioenergetic. (1st June 2022) - Gavini, J; Leuenberger, D; Yarahmadov, T; Dommann, N; Keogh, A; Melin, N; Tschan, M; Nuoffer, J-M; Hertig, D; Zuber, B; Odriozola, A; Tombolini, R; et al.
Abstract: Objective: Circulating Proprotein convertase subtilisin/kexin type 9 (PCSK9) captured the scientific community's attention as powerful target to fight against high serum cholesterol and its associated adverse consequences. Despite the well-described role of PCSK9 in impairing the recycling of low-density lipoprotein receptor (LDLR) on hepatocytes, its intracellular importance in metabolism modulations remain largely unexplored. Here, we describe a novel intracellular function of PCSK9 in hepatocyte metabolism and in liver regeneration. Methods: A surgical model of partial hepatectomy (PH) was used to induce liver cell proliferation and serological and histological lipo- and glyco-metabolic perturbations were investigated in PCSK9 knockout and wild-type mice before and after PH. Mitochondrial bioenergetic level, compartmental architecture as well as intracellular localization and function of PCSK9 were further analyzed in vitro on murine primary isolated hepatocytes and PCSK9 lentiviral knockdown human liver cancer cell lines. Results: Loss of PCSK9 expression led to a basal higher mitochondrial bioenergetic status in hepatocytes, characterized by a profound remodeling of mitochondrial architecture. Livers from PCSK9 knockout mice displayed a diffuse oxidative stress and a significant upregulation of cellular detoxification and superoxide radicals removal genes induced by the activation of c-Jun N-terminal kinase (JNK) pathway before PH. PCSK9 deficient mice showed a primed compensatory hepatic hyperplasia after PH, accompanied by an earlier transient regeneration-associated steatosis due to a higher LDLR expression and cholesterol uptake, with an increased β-oxidation, gluconeogenesis and glycolysis rate. Tetramethylrhodamine ethyl ester staining of isolated hepatocytes and liver cancer PCSK9 knockdown clones revealed a significantly reduced mitochondrial membrane potential when compared to controls. Confocal live-cell imaging and proteins immunoprecipitation showed respectively a mitochondrial recruitment of PCSK9 in proliferating cells and its interaction with mitochondrial membrane carriers and chaperons. Conclusion: Despite the role played by circulating PCSK9 in regulating systemic cholesterol levels, our data shed light on its intracellular impact on mitochondrial architecture, membrane polarization and related metabolic perturbations in compartmental bioenergetics.